Psychophysiological influences on personality trajectories in adolescent females exposed to child maltreatment. (October 2020) - Hassan, Raha; MacMillan, Harriet L.; Tanaka, Masako; Schmidt, Louis A.
Abstract: Although child maltreatment is a major public health concern, which adversely affects psychological and physical development, we know relatively little concerning psychophysiological and personality factors that may modify risk in children exposed to maltreatment. Using a three-wave, short-term prospective design, we examined the influence of individual differences in two disparate psychophysiological measures of risk (i.e., resting frontal brain electrical activity and respiratory sinus arrhythmia) on the trajectories of extraversion and neuroticism in a sample of female adolescents ( N = 55; M age = 14.02 years) exposed to child maltreatment. Adolescents exposed to child maltreatment with relatively higher left frontal absolute alpha power (i.e., lower brain activity) at rest exhibited increasing trajectories of extraversion, and adolescents exposed to child maltreatment with relatively lower respiratory sinus arrhythmia at rest displayed increasing trajectories of neuroticism over 1 year. Individual differences in psychophysiological measures indexing resting central and peripheral nervous system activity may therefore differentially influence personality characteristics in adolescent females exposed to child maltreatment.